Soil nutrient stock dynamics and land-use management of annuals, perennials and pastures after slash-and-burn in the Southern Ecuadorian Andes - Chamba Zaragocin, D. (2017)
Quantification of nutrient stocks and their temporal changes are considered of prime importance in farming systems of the humid tropics to answer the question of sustainable management. The research area in the Southern Ecuadorian Andes included forest, annual (0-5 years old) and different aged perennial (0-5, 6-10, 11-20, 21-30) and pasture (0-5, 6-10, 11-20, 21-30, >30) sites. Soil organic carbon (SOC), total and plant available soil nutrient stocks and nutrient balances were investigated to assess temporal soil nutrient dynamics in relation to management activities. Forest conversion by slash-and-burn caused a decrease in SOC stocks in all three land-uses amounting between 14% and 19%. This was mainly due to the absence of an organic layer and losses in the upper five cm of the mineral soil. Stocks of exchangeable bases and pH values increased in annuals which however, had the most negative nutrient balance of all land-uses amounting to -128, -25 and -226kgha-1a-1 for N, P and K, respectively. The abandonment of annual sites after five years was linked to a shortage of available N and P due to low-external-input management which caused SOC stock decreases. Major soil nutrient changes in perennials and pastures did not occur directly but 6-20 years after forest conversion with increases in stocks for total N, P, S and exchangeable bases above forest level. SOC stocks of medium aged perennials and pastures increased above forest level in the mineral soil. Easily available inorganic N and P stocks remained low throughout the chronosequence in perennials and pastures, indicating a quick uptake by plant roots and microorganisms. Compared to medium aged sites, oldest perennials and pastures showed a strong decrease in SOC (-28% and -16%) and soil nutrient stocks. Stocks for total N, P, S and exchangeable bases were up to 50% below those of medium aged sites in oldest perennials and pastures